Essential practices for managing chemical reactivity hazards - Johnson, Robert W. (Robert William), 1955- (CCPS concept book., 2003)
In its recent investigation of chemical reactivity accidents, the US Chemical Safety Board noted a gap in technical guidance and regulatory coverage. This volume closes the gap in technical guidance, helping small and large companies alike identify, address, and manage chemical reactivity hazards. It guides the reader through an analysis of the potential for chemical reactivity accidents to help prevent fires, explosions, toxic chemical releases or chemical spills. This volume is applicable to processes at any scale and is particularly useful for chemists, safety managers, and engineers involved in scale-up. An enclosed CD-ROM provides portable checklists, analysis tools, and a list of additional references. Special Details: Electronic Copy available free of charge. Visit http://www.aiche.org/ccps/resources.htm for details. To Purchase a Bound Copy click "Add to Cart" above. Note: CD-ROM/DVD and other supplementary materials are not included as part of eBook file